Paradoxical leadership: a meta-analytical review - Lee, Allan; Lyubovnikova, Joanne; Zheng, Yaxin; Li, Zexi Flavia (Frontiers in Organizational Psychology, 2023)
The past few decades have brought a rapid emergence of research related to paradoxical leadership behavior (PLB), yet extant research remains scattered, inconsistent and somewhat contradictory. This meta-analysis examines the association between PLB and follower/team outcomes, specifically exploring PLBs incremental validity over other established leadership styles, namely transactional, transformational and servant leadership, as well three competing mechanisms through which PLB elicits positive effects. Our findings demonstrate that PLB is consistently positively associated with follower in-role performance, organizational citizenship behaviour, creativity, voice and innovation. However, while PLB showed consistent incremental effects over transactional leadership, its incremental validity in relation to transformational and servant leadership is less clear, with the exception of predicting innovation. Finally, we found evidence that PLB is related to follower behaviors via socio-cognitive (psychological safety), role-based (role clarity), and relational (LMX) mechanisms, with these effects varying as a function of the outcome. Based on our findings, we derive several important implications for PLB theory and key implications for future research.